2006
DOI: 10.1002/bit.21271
|View full text |Cite
|
Sign up to set email alerts
|

A simplified bioprocess for human alpha‐fetoprotein production from inclusion bodies

Abstract: A simple and effective Escherichia coli (E. coli) bioprocess is demonstrated for the preparation of recombinant human alpha-fetoprotein (rhAFP), a pharmaceutically promising protein that has important immunomodulatory functions. The new rhAFP process employs only unit operations that are easy to scale and validate, and reduces the complexity embedded in existing inclusion body processing methods. A key requirement in the establishment of this process was the attainment of high purity rhAFP prior to protein ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…This result was corresponding with other researches [44]. Leoing found that the amount of protein recovered in a native form was highly dependent on the ratio of the denatured protein and in his study, 50-fold dilution of target protein was found to be most favorable to increase protein solubility [23]. Hwang pointed out that high refolding yield (>70%) could be easily achieved at a refolding protein concentration of 30µg/mL [21].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result was corresponding with other researches [44]. Leoing found that the amount of protein recovered in a native form was highly dependent on the ratio of the denatured protein and in his study, 50-fold dilution of target protein was found to be most favorable to increase protein solubility [23]. Hwang pointed out that high refolding yield (>70%) could be easily achieved at a refolding protein concentration of 30µg/mL [21].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, contaminants, especially hydrophobic proteins and lipids, are expected to bind to target proteins after refolding [21]. This highlights the importance of product purification before the critical refolding step [23]. Thus, the sediment was dissolved in 8 M urea.…”
Section: Purification Of Two Recombinant Caifnα Fusion Proteinsmentioning
confidence: 99%
“…hBDs are cysteine-rich and disulfide bonds have been suggested to be important for tertiary structure stabilisation of ␤-defensins [35][36][37]. Therefore, optimising the refolding buffer with respect to redox environment is considered important to enhance oxido-shuffling cysteines and hence promote correct formation of disulfide bonds [38,39]. The effect of varying GSH:GSSG ratio in the refolding buffer on the antimicrobial activity of hBD25 was investigated.…”
Section: Antimicrobial Activity Determination Of Hbd25mentioning
confidence: 99%
“…Evidence that PMP was retained on the retentate side of the filter was provided by SDS-PAGE analyses which indicated roughly the same PMP concentration in all retentate samples collected from the different wash experiments (data not shown). Consequently, urea/phos8/EDTA was excluded as an optimal wash solution, because the inclusion bodies were partly dissolved and also because the risk of carbamylation of the product protein with use of urea (Leong and Middelberg, 2007).…”
Section: Separation Of Soluble Contaminantsmentioning
confidence: 99%
“…IBs, cell debris, host cell proteins (HCP), host DNA, and endotoxin. It is known that residual contaminants may negatively affect the renaturation performance (Shire et al, 1984;Maachupalli-Reddy et al, 1997;Thatcher and Hitchcock, 1994;Batas et al, 1999;Leong and Middelberg, 2007).…”
Section: Introductionmentioning
confidence: 99%